The role of the prooxidative-antioxidative system in dentistry - Agnieszka Markowska-Dyner (Kazimierz Wielki University, 2018)
During physiological processes, a number of chemical reactions take place in all cells including oxidation and reduction.Those reactions can result in the production of free radicals, ie., atoms or atom groupsthat have one or more unpaired electrons and thereforeextremely high chemical reactivity. Numerous free radicals are formed through natural processes; the levels of free radicals in the cell depends, among others, on physical activity, environmental factors (eg., ionizing radiation from natural or artificial sources, toxins such as exhaust fumes) and lifestyle-relatedstress. Generation of free radicals is associated with oxidative and nitrosative stress. Oxidative stress is defined as a disturbance in cell homeostasis leading to an increase in reactive oxygen species (ROS). It is also a disturbance in the balance between oxidation processes and antioxidant defenses.